An unusual method to diagnose a rare disease: Upper gastrointestinal endoscopy - Tolga Düzenli; Mustafa Kaplan; Alpaslan Tanoğlu; Musa Salmanoğlu (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Düzenli T, Kaplan M, Tanoğlu A, Salmanoğlu M. An unusual method to diagnose a rare disease: upper gastrointestinal endoscopy. Turk J Gastroenterol 2017; 28: 522-3.